2010
DOI: 10.1159/000320413
|View full text |Cite
|
Sign up to set email alerts
|

State-of-the-Art: Immunosuppression and Biologic Therapy

Abstract: Azathioprine and 6-mercaptopurine are orally administered immunosuppressive drugs which are effective for the treatment of Crohn’s disease and ulcerative colitis. Azathioprine is rapidly converted to 6-mercaptopurine after administration. 6-Mercaptopurine is then either converted to the putative active metabolites, the 6-thioguinine nucleotides, or inactivated by the enzyme xanthine oxidase to 6-thiouric acid or alternatively inactivated to 6-methylmercaptopurine by the enzyme thiopurine methyltransferase. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 71 publications
0
20
0
1
Order By: Relevance
“…In contrast, a case control study at the Mayo Clinic found an increased risk of serious infection from combination therapy compared to infliximab monotherapy, as well as an increased odds of serious infection from infliximab, corticosteroids, and azathioprine/6MP alone compared to no medication [4]. Although these two well-known studies have conflicting results, the differences have been explained as likely due to the different patient populations [55]. Crohn’s disease (CD) is associated with more disease related infectious complications (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a case control study at the Mayo Clinic found an increased risk of serious infection from combination therapy compared to infliximab monotherapy, as well as an increased odds of serious infection from infliximab, corticosteroids, and azathioprine/6MP alone compared to no medication [4]. Although these two well-known studies have conflicting results, the differences have been explained as likely due to the different patient populations [55]. Crohn’s disease (CD) is associated with more disease related infectious complications (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their impressive efficacy, the use of these antibodies is associated with an increased risk of serious side effects, including the reactivation of tuberculosis, opportunistic infections and a long-term risk of malignancy. These side effects result from systemic immunosuppression as a consequence of the inhibition of TNF’s host defense functions 8,9 . An ideal anti-TNF antibody therapy for IBD would deliver antibodies directly to the site of inflammation in the gut while avoiding systemic exposure and immunosuppression.…”
mentioning
confidence: 99%
“…Monoclonal antibodies anti-Tumour Necrosis Factor alpha mechanism of action includes the neutralization of both soluble and transmembrane portion of this molecule; also neutralizes Tumour Necrosis Factor alpha-producing (Sandborn, 2010;Smolen, 2011). Monoclonal antibodies anti-Tumour Necrosis Factor alpha were first used in the treatment of Crohn's disease but have been used successfully in severe, unresponsive to treatment Ulcerative Colitis or as rescue therapy (Hoentjen & van Bodegraven, 2009;Lees et al 2007).…”
Section: Biological Therapiesmentioning
confidence: 99%